Maximal strength, sprint and jump performance in elite kumite karatekas - Cinarli, F. S.; Aydogdu, O.; Aydin, Y.; Tokgöz, G.; Kahraman, A.; Beykumül, A.; Aygoren, C.; Yilmaz, N.; Ramirez-Campillo , R. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background Both maximal muscle strength and muscle power are independently important for karatekas. However, the relationship between strength and power in elite male kumite karatekas is under researched. This study aimed to determine the relationship between back-leg-chest (BLC) isometric muscle strength with sprint and jump variables in elite male karatekas.